Nutrients and heavy metal removal from landfill leachate by sub-surface flow (SSF) constructed wetlands planted with Limnocharis Flava and Scirpus Atrovirens - Nor Shazwani, Ismail (Universiti Malaysia Perlis (UniMAP), 2013)
Access is limited to UniMAP community.